A study exploring the relationship of secondary school teacher attitudes and efficacy beliefs to inclusive behaviours towards young people with social, emotional and mental health (SEMH) needs. - Cronin, John (2022)
The inclusion of Children and Young People (CYP) with Social, Emotional and Mental Health (SEMH) difficulties has proven to be an ongoing challenge for teachers and schools in the UK; teachers view CYP with SEMH-type needs as the most challenging area of Special Educational Need (SEN) to include in mainstream classes (De Boer et al., 2011; DfE, 2019b; Dimitrelllou, 2017) and schools disproportionately exclude CYP with SEMH-type needs compared to other areas of SEN or no SEN at all (Bryant et al., 2018; DfE, 2019b; Graham et al., 2019; Monsen et al., 2014). Despite the government’s commitment to supporting the prevention and effective management of young people’s mental health needs (DoH and DfE, 2017; DfE, 2018; DfE, 2019a), SEMH difficulties are highly prevalent and are expected to increase as a result of the disruption caused by the Covid-19 pandemic (Lee, 2020), placing even greater focus on schools to promote the successful inclusion of students with these needs.